Sistema Experto para la Optimización de la Gestión Académicos en la Subdirección de la Universidad Técnica de Cotopaxi - Extensión La Maná. - Aviles Cortez, Erika Patricia (2020)
The main purpose of the research work is to collaborate with the solution to the problems presented by the Universidad Técnica de Cotopaxi (UTC), La Maná at the beginning of the cycle with respect to the management of academic schedules (GHA), for this reason, the following is described in a specific way: To design a prototype of an expert system using artificial intelligence (AI) technique for the assignment of academic hours of teachers in an optimal and workable order, in such a way that the costs of material resources, time and human resources are minimized. Commonly the institutions of higher education and even postgraduate have focused their research in this area, however, until now it is not confirmed of an algorithm that provides complete and optimal solution due to its complexity. The technique used is the Genetic Algorithm (GA) of search based on natural genetics to find approximate optimums in computational tasks. It was handled with collaborative tools for coding in Python, the latter for its popularity in AI programming, using mainly the libraries: Genetic, for mathematical processing and Tkinder, for the design of the graphical interface. The research started through a search in the literature and the contribution of the results in similar works. In order to penetrate the problem, an in-situ interview was held, information necessary to establish the needs of the institution and to define the limitations to be considered. Finally, configurations of the parameters of the implemented GA were made, reaching favorable results that show that, in effect, the technique of the GA allows good solutions with respect to the assignment of hours in a manual way and therefore the software can be easily adapted to the GHA.